Pragmatic Failure of Students Conversation in Speaking Class - Ahmad Tauchid; Era Tri Nur Era Tri Nur Kumala; Alfi Nika Rizkiana (Institut Agama Islam Negeri Palopo, 2022)
When communicating with others, people may be unable to distinguish between speaker and hearer, yet the dialogue can continue. As a result, a pragmatic role is required. Nonetheless, many pragmatic examples may fail for various reasons, including cross-cultural comprehension and even grammatical form misinterpretation. This situation occurs not just in real life but also in the classroom. This essay aims to examine the pragmatics of English students' dialogue in speaking class. The conversation in speaking class begins with a definition of the Pragmatic and Speech Act and Pragmatic Failures. It will be followed by examining several pragmatic failure dialogues in an EFL speaking class. According to this study, there are ten pragmatic failure discussions. The researchers discovered the following situations based on those conversations: first, there are different types of speech acts in English students' conversations in the speaking class, such as directive, assertive, and proclamation, which are all based on Levinson's theory. Furthermore, pragmatic failure occurs in English students' conversations in speaking class and is referred to as pragmalinguistics failure.